2015
DOI: 10.1177/0265532215590694
|View full text |Cite
|
Sign up to set email alerts
|

Removing bias towards World Englishes: The development of a Rater Attitude Instrument using Indian English as a stimulus

Abstract: This study explores the attitudes of raters of English speaking tests towards the global spread of English and the challenges in rating speakers of Indian English in descriptive speaking tasks. The claims put forward by language attitude studies indicate a validity issue in English speaking tests: listeners tend to hold negative attitudes towards speakers of non-standard English, and judge them unfavorably. As there are no adequate measures of listener/rater attitude towards emerging varieties of English in la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…The instrument of the present study was taken from Hamid (2014) and Hsu (2016) and modified by Monfared (2020) about participants' view on WE in English proficiency such as TOEFL and IELTS. The questionnaire used likert scale to measure the answer, 1strongly disagree; 2disagree; 3moderately disagree; 4moderately agree; 5agree; 6strongly agree.…”
Section: Methodsmentioning
confidence: 99%
“…The instrument of the present study was taken from Hamid (2014) and Hsu (2016) and modified by Monfared (2020) about participants' view on WE in English proficiency such as TOEFL and IELTS. The questionnaire used likert scale to measure the answer, 1strongly disagree; 2disagree; 3moderately disagree; 4moderately agree; 5agree; 6strongly agree.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown how native-speakerism is still concerning from both sides; the learners (Hendriks et al, 2021;Hsu, 2016;Lee & Warren Green, 2016;Tamimi Sa'd, 2018) and the instructors (Dogancay-Aktuna & Hardman, 2018). Hendriks et al (2021) share learners' attitudes toward their lecturers who teach with non-native accented speaking.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The findings show that the non-native accented lecturers were perceived negatively than lecturers with a native accent. Hsu (2016) conducted a study with the collaboration of English testing raters in India and found out that the raters more likely to value test-takers who speak in American or British English. Lee & Warren Green (2016) in South Korea state that it is easier to recognize native-accented speaking than any English variations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The rater attitude instrument (RAI) has been discussed in detail in Hsu (2016). This section will provide a brief summary of the RAI and highlight the aspects that are relevant to the current study.…”
Section: Rater Attitude Instrument In Language Testingmentioning
confidence: 99%
“…Questions about bias on the part of raters towards the varieties of English in the world today are arising in the relevant discussions (Davies et al 2003). Studies have investigated the impact of rater nationality on speaking test scores (Chalhoub-Deville and Wigglesworth 2005;Hamp-Lyons and Zhang 2001), differences in scores due to rater attitudes towards Korean English (Kim 2005), and the recent development of a "rater attitude instrument" that measures raters' attitudes towards WE (Hsu 2016). The emerging agenda on rater psychological traits and attitude-behavior relationship includes broad concerns about the impact of WE on English speaking test scores, score validity (Davies et al 2003), fairness (Kunnan 2004), and unexpected consequences of test use (Davidson 2006).…”
Section: Introductionmentioning
confidence: 99%